Pengaruh Asimetri Informasi Terhadap Kesenjangan Anggaran Dengan Locus Of Control Sebagai Variabel Moderasi Pada Kantor Bupati Dharmasraya - Yuskam, Rica Putri; Salfadri, Salfadri; Nancy, Delori (Jurnal Riset dan Sains Ekonomi, 2024)
This study discusses the effect of information asymmetry on budget gaps with locus of control as a moderating variable at the Dharmasraya Regent's office. Data processing in this research is using a moderation regression model (moderation regression analysis). The source of data in this study is primary data obtained directly from research respondents through distributed questionnaires. The sample taken in this study used a total sampling technique. The results of the analysis of this study indicate that the information asymmetry variable has a partial positive effect on the budget at the Dharmasraya Regent's Office with a significant (0.000 < 0.05). The locus of control variable strengthens the effect of Information Asymmetry on the Budgetary Gap. With a significant value less than (0.000 < 0.05). Keywords : Effect of Information Asymmetry, Budget Slack, Locus Of Control, Dharmasraya Regent's Office